Emergence of linezolid resistance in hepatobiliary infections caused by Enterococcus faecium. Issue 2 (February 2016) - Niebel, Marc; Perera, M. Thamara P. R.; Shah, Tahir; Marudanayagam, Ravi; Martin, Kate; Oppenheim, Beryl A.; David, Miruna D.
Abstract : Enterococcal infections are common in liver transplantation and hepatopancreaticobiliary (HPB) surgery. Linezolid is frequently used to treat not only vancomycin‐resistant Enterococcus (VRE), but also vancomycin‐sensitive Enterococcus (VSE) infections, and resistance can develop. This study evaluated all the Liver Unit patients who developed infections with linezolid‐resistant Enterococcus (LRE) in order to elicit the association with prior linezolid usage, to explore possible risk factors for infection, and to better understand the epidemiology of these isolates in this patient group. Between 2010 and 2015, infections with LRE developed in 10 patients (8 following liver transplantation and 2 following HPB surgery) after 22‐108 days of treatment. Selected pulsed‐field gel electrophoresis demonstrated that 2 out of 10 patients were cocolonized with different strains and indicated that cross‐transmission may have occurred. In conclusion, in this group of patients with complex hepatobiliary infections, the optimal antibiotic strategies for the treatment of Enterococcus faecium infections are not clearly defined, and there is a significant risk of emergence of resistance to linezolid in E. faecium after exposure to this agent in patients, especially in the presence of a deep source of infection on a background of hepatic artery insufficiency. Caution is needed when using prolonged courses of linezolid in this setting, and further studies are necessary to determine the optimum treatment. Liver Transpl 22:201‐208, 2016 . © 2015 AASLD.